2020
DOI: 10.1021/acs.jmedchem.9b02038
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1, a Central but Unexploited Target: Advances in Its Physiological/Pathogenic Functions and Small Molecular Modulators

Abstract: p62/SQSTM1, encoded by gene SQSTM1, is widely known as an adaptor protein of selective autophagy to promote aggregate-prone proteins for degradation. It is also a stress-induced scaffold protein involved in Nrf2 activation to resist oxidative stress. Multiple domains of p62 interact with several essential pathways implicated in cell differentiation and proliferation, placing p62 at a significant position to mediate cell survival and apoptosis. The p62 protein has been suggested as a potential target in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 210 publications
1
17
0
Order By: Relevance
“…The level of p62 is widely used as an indicator of autophagic flux. Suppression or decline of autophagy is always accompanied by the accumulation of p62 (Chen et al, 2020). We observed the morphology and structure of autophagic vesicles using transmission electron microscopy, and found that morphine tolerance induced the ac- Minocycline, a tetracycline antibiotic, has immunomodulatory effects beyond its antibacterial activity, including anti-inflammatory, anti-apoptotic and neuroprotective properties (Garrido-Mesa et al, 2013;Tikka & Koistinaho, 2001;Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The level of p62 is widely used as an indicator of autophagic flux. Suppression or decline of autophagy is always accompanied by the accumulation of p62 (Chen et al, 2020). We observed the morphology and structure of autophagic vesicles using transmission electron microscopy, and found that morphine tolerance induced the ac- Minocycline, a tetracycline antibiotic, has immunomodulatory effects beyond its antibacterial activity, including anti-inflammatory, anti-apoptotic and neuroprotective properties (Garrido-Mesa et al, 2013;Tikka & Koistinaho, 2001;Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…The level of p62 is widely used as an indicator of autophagic flux. Suppression or decline of autophagy is always accompanied by the accumulation of p62 (Chen et al., 2020). We observed the morphology and structure of autophagic vesicles using transmission electron microscopy, and found that morphine tolerance induced the accumulation of autophagic vacuoles in spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study revealed that oligomerized p62 targeted to the autophagosome formation site independent of LC3 (25). A recent study showed that p62 protein expression was not associated with autophagy under specific conditions (26), while p62 protein has also been shown to promote tumor cell survival by activation of the NF-kb pathway (27). The latest study revealed that p62 expression might target PD-L1, and p62 signaling axis could be useful to suppress the EGFR-TKIresistant lung cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity [71]. p62/SQSTM1 plays a crucial part in the oxidative stress response pathway through its direct association with the ubiquitin ligase adaptor Kelch-like ECH-associated protein 1 (Keap-1), resulting in Nrf2 activation [51].…”
Section: Discussionmentioning
confidence: 99%